Occupational exposure to Aspergillus and aflatoxins among food-grain workers in India. (July 2014) - Malik, Abida; Ali, Sana; Shahid, Mohd; Bhargava, Rakesh
Abstract : Background: Aflatoxins are a metabolite of Aspergillus molds and are widespread in the natural environment. Workers who handle food grains are at increased risk of exposure to aflatoxins and subsequently certain respiratory conditions. In India, more than half of the employed population is engaged in some type of agricultural work, yet little known about the respiratory problems as a result of exposure to aflatoxins among workers who handle food grains in India. Objectives: The aim of this study was to determine the risk of occupational exposure to aflatoxins in food-grain workers compared to workers who are not occupationally exposed to food grains. Methods: Bronchoalveolar lavage (BAL) and serum samples from 46 food-grain workers and 44 non-food-grain workers were analyzed for the presence of aflatoxins. Microscopy and culture of BAL samples were performed to detect Aspergillus species. Results: Aflatoxins were detected in 32·6% of the food-grain workers and 9·1% of non food grain workers ( P <0·01). A significant difference was also found in BAL culture for Aspergillus ( P <0·01) between the two groups. About 47·8% of the food-grain workers and 11·4% of non-food-grain workers had chronic respiratory symptoms. Conclusion: Occupational exposure to aflatoxins in food-grain workers was found to be associated with the increased presence of respiratory symptoms.